Electro-active polymer actuator based on pre-stretched polyurethane - Quek, Sebastian El Fin. (2012)
Dielectric elastomer actuators (DEA) have been studied extensively as it has shown to generate rather promising results in the laboratory for muscle-like actuation. This project investigates how pre-stretching affects the performance of polyurethane (in particular TPU 58887 Elastomer (Estane) and Deerfield PT6100S) as a dielectric material in a basic DEA configuration. Pre-stretching seems to affect the actuated area strain both positively and negatively. The optimal pre-stretch percentage for TPU 58887 Elastomer (Estane) and Deerfield PT6100S has been found to be 40% and 15% respectively where the positive effects of pre-stretching outweigh the negative effects. The maximum area strain generated is 3.05% and 0.437% for TPU 58887 (Estane) and Deerfield PT6100S respectively. A higher pre-stretch percentage leads to a higher breakdown strength and a lower breakdown voltage.